Metodologi Tafsir Fi Zhilal al-Qur'an Sayyid Qutb - Mutia Lestari; Susanti Vera (UIN Sunan Gunung Djati Bandung, 2021)
The dynamics of interpretation in the knowledge of exegesis have continued to develop from the early period of interpretation to the present day. Various methods and approaches are continuously carried out in an effort to create a comprehensive study in various paradigms. Each commentary book has its own methodology and mission to greet its readers. This methodology serves as an initial introduction to understanding the content and mission expected by the interpreter. Thus, knowing the methodology and purpose of a commentary book is a must. Sayyid Qutb's Tafsir Fi zhilalil Quran was present as a response to Muslims who were facing the progress of the times, he positioned himself as an intermediary to always stick to the teachings of the Koran and reject the government system which he judged to be far from spiritual values. The purpose of this research is to discuss the methodology and mission of Sayyid Qutb's Fi Zhilalil Quran interpretation. This type of research is qualitative through literature study, with primary and secondary source analysis. The result of this research is Tafsir Fi Zhilalil Quran by Sayyid Qutb is a bi al-Ma'tsur interpretation, the method used is tahlili with the style of the Muslim liberation movement. The approach used by Sayyid Qutb is a linguistic and social approach.